Influence of tidal turbine control on performance and loads. (September 2021) - Nambiar, Anup; Draycott, Samuel; Payne, Grégory S.; Sellar, Brian; Kiprakis, Aristides
Abstract: Tidal stream turbines (TST) are subject to large unsteady hydrodynamic loads which will result in fatigue of components and potentially failure. Control algorithms, if used effectively, have the ability to reduce these unsteady loads without affecting overall performance. To examine the effect of control strategy on performance and loads, experimental tests were carried out using a 1:15 scale TST in a combined wave–current facility. Loose and stiff speed controllers were developed and implemented, in addition to torque control, and tested for a range of tip-speed-ratios in a fixed inflow velocity. The speed controllers are additionally tested under regular, irregular and focused wave conditions. Through time and frequency-domain analysis, it is demonstrated that looser controllers, through larger speed variations, induce larger variations in the streamwise forces (rotor thrust and root bending moment), but smaller variations in torque. Similarly, larger extremes are recorded for streamwise forces under looser controllers. Mean values and hence overall turbine performance is found to be unchanged. It is noted that for the wave cases tested the controllers do not significantly affect the streamwise forces; likely a result of the large wave-induced velocities dominating the resulting blade angles-of-attack. Additionally, for some rotational speed values significant amplification of mechanical vibrations are observed. These results highlight the complexities associated with controller choice; considering the trade-offs in torque and thrust variations, potential mechanical resonance, and varying performance depending on the flow conditions. Proper appreciation of these considerations will be vital as we move towards commercial arrays of devices which must be controlled optimally to maximise performance whilst minimising loading and associated O&M costs.